2013
DOI: 10.1155/2013/737580
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Delivery of the VEGF and BMP-6 Genes to Rat Mesenchymal Stem Cells Potentiates Osteogenesis

Abstract: The combined delivery of mesenchymal stem cells (MSCs), vascular endothelial growth factor (VEGF), and bone morphogenetic protein (BMP) to sites of bone injury results in enhanced repair compared to the administration of a single factor or a combination of two factors. Based on these findings, we hypothesized that coexpression of VEGF and BMP-6 genes would enhance the osteoblastic differentiation of rat bone-marrow-derived stem cells (rMSCs) and osteogenesis by comparison to rMSCs that do not express VEGF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The transfected cells dramatically increased new bone formation and angiogenesis 5 weeks after surgery when compared to the nontransfected MSCs. Seamon et al [2013] subcutaneously injected MSCs transduced with adenoviral vector (Ad-VEGF + BMP-6) in rats. Analysis showed that only gene-transduced MSCs could induce osteogenesis in vivo, whereas adenoviral vector or nontransduced MSCs alone did not induce osteogenesis.…”
Section: Future Directions Of Msc Therapy In Clinical Practicementioning
confidence: 99%
“…The transfected cells dramatically increased new bone formation and angiogenesis 5 weeks after surgery when compared to the nontransfected MSCs. Seamon et al [2013] subcutaneously injected MSCs transduced with adenoviral vector (Ad-VEGF + BMP-6) in rats. Analysis showed that only gene-transduced MSCs could induce osteogenesis in vivo, whereas adenoviral vector or nontransduced MSCs alone did not induce osteogenesis.…”
Section: Future Directions Of Msc Therapy In Clinical Practicementioning
confidence: 99%
“…Earlier we demonstrated that cloned MSCs transiently expressing VEGF and BMP‐6 genes, or VEGF and LMP‐1 genes, induce significantly greater osteogenesis in vivo than that induced by MSCs alone or MSCs expressing only one gene (Cui et al, ; Wang et al, ). We have also shown that primary MSCs fail to induce ectopic bone formation but adenoviral transfer of the VEGF and BMP‐6 genes enables these MSCs to induce bone formation successfully (Seamon et al, ). Moreover, we demonstrated that the addition of VEGF and BMP‐6 proteins to culture medium enhanced osteogenic differentiation of mouse bone marrow‐derived MSCs (Madhu et al, ) and hADSCs in vitro (Zhang et al, ).…”
mentioning
confidence: 99%
“…Genetic engineering approaches have been extensively explored to endow MSCs with enhanced regenerative capabilities to repair bone defects. A number of studies have demonstrated that the genetic modification of MSCs by the forced expression of various pro‐regenerative factors, such as BMP‐2, TGF‐β1, VEGF, and bFGF, improved bone formation and the repair of bone defects (Carpenter et al, 2010; Peng & Wang, 2017; Seamon et al, 2013). With the identification of an increasing number of miRNAs involved in osteogenesis, miRNA manipulation has become an important strategy for bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…in mediating the enhanced osteogenic differentiation of hASCs by miR-146a suppression. improved bone formation and the repair of bone defects (Carpenter et al, 2010;Peng & Wang, 2017;Seamon et al, 2013). With the identification of an increasing number of miRNAs involved in osteogenesis, miRNA manipulation has become an important strategy for bone repair.…”
Section: Effects Of Immunomodulatory Products From Mir-146as-transdmentioning
confidence: 99%